THE INNOVATION OF DIGITAL LEARNING MEDIA IN ISLAMIC RELIGIOUS EDUCATION TO IMPROVE STUDENTS’ LEARNING MOTIVATION - Siti Akhidatul Musrifah; Prawidya Lestari (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
This study examines the innovation of digital-based Islamic Religious Education learning media and its role in enhancing students’ learning motivation at SMA Darul Hikmah Islamic School, Kutoarjo. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving the principal, teachers, and students, and analyzed using an interactive model with triangulation to ensure data validity. The findings indicate that digital media are integrated through Chromebooks, Interactive Flat Panels, a Learning Management System (Edunaf), multimedia content, and artificial intelligence-based applications such as NotebookLM. These innovations have been shown to improve students’ motivation to learn, particularly interest, attention, and engagement, while also facilitating understanding of abstract concepts. The novelty of this study lies in the integration of multiple digital platforms within a unified PAI learning ecosystem in a boarding school context, the emphasis on the affective dimension of motivation, and the implementation of a hybrid learning model that combines digital and traditional approaches. These findings highlight the transformative potential of digital media in creating adaptive, interactive, and sustainable PAI learning.